Application of Safety Briefing as an Effort to Reduce the Impact of Disasters in Health Care Facilities - Nurlaili, Ana; Mulyadi, Arif (Poltekkes Kemenkes Malang, Campus III Blitar, 2024)
Disasters can occur anywhere, including in community health service centers. Disasters in public health service centers can occur due to natural disasters but can also be caused by occupational accidents, due to the failure of occupational safety and health programs, poor physical planning of buildings, and the absence of care and supervision of sources of danger. The aim of this Revew study is to describe the implementation of safety briefing as an effort to reduce the impact of disasters in health care facilities (FASYANKES). Traditional literature review research methods and research design library research. Data were obtained from 5 research journals that have ISSN (International Standard Serial Number) and have a DOI (Digital Objective Identifier) by comparing or looking for similarities in the contents of research journals then discussing them. The results show that safety briefings are more influential in improving patient safety than some general hospital patient safety practices and show that safety briefings achieve beneficial results and can enhance safety culture.